Clinical activity of ipilimumab for metastatic uveal melanoma. Issue 20 (2nd August 2013) - Luke, Jason J.; Callahan, Margaret K.; Postow, Michael A.; Romano, Emanuela; Ramaiya, Nikhil; Bluth, Mark; Giobbie‐Hurder, Anita; Lawrence, Donald P.; Ibrahim, Nageatte; Ott, Patrick A.; Flaherty, Keith T.; Sullivan, Ryan J.; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Uveal melanoma exhibits a high incidence of metastases; and, to date, there is no systemic therapy that clearly improves outcomes. The anticytotoxic T‐lymphocyte–associated protein 4 (anti‐CTLA‐4) antibody ipilimumab is a standard of care for metastatic melanoma; however, the clinical activity of CTLA‐4 inhibition in patients with metastatic uveal melanoma is poorly defined. METHODS To assess ipilimumab in this setting, the authors performed a multicenter, retrospective analysis of 4 hospitals in the United States and Europe. Clinical characteristics, toxicities, and radiographic disease burden, as determined by central, blinded radiology review, were evaluated. RESULTS Thirty‐nine patients with uveal melanoma were identified, including 34 patients who received 3 mg/kg ipilimumab and 5 who received 10 mg/kg ipilimumab. Immune‐related response criteria and modified World Health Organization criteria were used to assess the response rate (RR) and the combined response plus stable disease (SD) rate after 12 weeks, after 23 weeks, and overall (median follow‐up, 50.4 weeks [12.6 months]). At week 12, the RR was 2.6%, and the response plus SD rate was 46.%; at week 23, the RR was 2.6%, and the response plus SD rate was 28.2%. There was 1 complete response and 1 late partial response (at 100 weeks after initial SD) for an immune‐related RR of 5.1%. Immune‐related adverse events were observed in 28 patients (71.8%) and included 7 (17.9%) grade 3 and 4 events. Immune‐related adverse events were more frequent in patients who received 10 mg/kg ipilimumab than in those who received 3 mg/kg ipilimumab. The median overall survival from the first dose of ipilimumab was 9.6 months (95% confidence interval, 6.3‐13.4 months; range, 1.6‐41.6 months). Performance status, lactate dehydrogenase level, and an absolute lymphocyte count ≥1000 cells/μL at week 7 were associated significantly with survival. CONCLUSIONS In this multicenter, retrospective analysis of 4 hospitals in the United States and Europe of patients with uveal melanoma, durable responses to ipilimumab and manageable toxicity were observed. Cancer 2013;119:3687–3695. © 2013 American Cancer Society.